2009
DOI: 10.3156/jsoft.21.640
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Development of Behavior Acquisition and Recognition based on Value System

Abstract: Abstract-Both self-learning architecture (embedded structure) and explicit/implicit teaching from other agents (environmental design issue) are necessary not only for one behavior learning but more seriously for life-time behavior learning. This paper presents a method for a robot to understand unfamiliar behavior shown by others through the collaboration between behavior acquisition and recognition of observed behavior, where the state value has an important role not simply for behavior acquisition (reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…From the view point of reinforcement learning framework, Meltzoff's "Like me" hypothesis indicates that a child estimates rewards received by his/her caregiver based on experiences of self. Estimation of rewards received during the observed behavior based on reward models of own behavior enables an agent to understand/recognize/learn the observed behavior deeply [6], [7]. View estimation is important to understand/imitate the observed behavior because the mapping from sensory information to motor skill would be based on an egocentric coordinate, not on an allocentric one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the view point of reinforcement learning framework, Meltzoff's "Like me" hypothesis indicates that a child estimates rewards received by his/her caregiver based on experiences of self. Estimation of rewards received during the observed behavior based on reward models of own behavior enables an agent to understand/recognize/learn the observed behavior deeply [6], [7]. View estimation is important to understand/imitate the observed behavior because the mapping from sensory information to motor skill would be based on an egocentric coordinate, not on an allocentric one.…”
Section: Discussionmentioning
confidence: 99%
“…From a viewpoint of reinforcement learning framework, this hypothesis indicates that the reward and state value of the demonstrator might be estimated through observing the behavior. Takahashi et al proposed a method to understand observed behavior based on the state value estimation [6] and a method for mutual development of acquisition and recognition of observed behavior [7]. From the above viewpoints, the TD error might be utilized not only for behavior learning but also for the view estimation.…”
Section: Introductionmentioning
confidence: 98%
“…The observed behaviours are chosen with respect to the similarity to the current situation. In [19] it is shown that not only the recognition of the observed action is important, but also to know the value of it. To acquire information from a demonstrator does not mean to replicate his movements, but to understand his intention and find a way to reach the same goal.…”
Section: Related Workmentioning
confidence: 99%